Medium / high-entropy metal organic framework material and preparation method thereof

The preparation of medium/high entropy metal organic frame materials by solid phase method solves the problem of difficult to control metal proportions and structural performance in the prior art, and achieves efficient and low-cost programmable preparation, and has excellent gas adsorption performance.

CN119842087AActive Publication Date: 2025-04-18WUHAN UNIV OF TECH

Patent Information

Application Number
CN202411829322.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

It is difficult to develop medium/high entropy metal organic frame materials with uniform proportions and controllable content in the prior art, and common preparation methods cannot accurately control the molar ratio and structural properties of metal elements.

Method used

The medium/high entropy metal organic frame material is prepared by solid phase method. By heating the mixture of metal compounds and organic ligands in an alumina crucible, the uniform distribution of metal ions and the sufficient reaction of the organic ligands are achieved, ensuring the entropy value and structural performance of the material.

Benefits of technology

The green, efficient, low-cost and programmable preparation of medium/high entropy metal organic frame materials is achieved, ensuring the high entropy state of the material and excellent gas adsorption performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842087A_ABST
    Figure CN119842087A_ABST
Patent Text Reader

Abstract

The invention provides a medium / high-entropy metal organic framework material and a preparation method thereof, the configuration entropy delta S of the medium-entropy metal organic framework material is greater than 1R and less than 1.5 R, and the configuration entropy delta Sgt of the high-entropy metal organic framework material is greater than 1R and less than 1.5 R; 1.5 R, R is a gas constant and is 8.314; metal ions in the medium / high-entropy metal organic framework material are at least four of magnesium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, molybdenum, ruthenium, palladium, silver, cadmium, indium, tin, iridium, rhodium and platinum, the molar weight of each metal ion is 10%-70% of the total molar weight of the metal ions, and the ratio of the total molar weight of the metal ions to the molar weight of the organic ligand is 1: (2-8). The preparation method has the characteristics of being programmable and adjustable, the number of metal types is four or more, and the metal proportion change of the metal content before and after preparation is smaller than 5%. The medium / high-entropy MOFs provided by the invention has the characteristics of uniform metal element distribution, accurate modulation and organic ligand replacement, and can accurately regulate and control the types and proportions of metals in the medium / high-entropy MOFs as well as the structure and performance of the obtained sample.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of cutting-edge new material technology, and in particular to a medium / high entropy metal organic framework material and a preparation method thereof. Background Art

[0002] Metal-organic frameworks (MOFs) are a new type of crystalline porous material with a periodic network structure formed by linking molecular building blocks to each other through strong chemical bonds. Its main structure is an inorganic-organic hybrid porous framework assembled by metal ions and organic ligands through chemical coordination, in which metal ions serve as nodes of the framework structure and organic ligands serve as bridging groups connecting these nodes. MOFs materials can be modified by mixing / replacing metal ions and organic ligands to design and control the structure and properties of the framework, making this type of material have the characteristics of diverse structures, rich pores, high specific area and easy functionalization. At the same time, medium / high entropy MOFs can be formed through a variety of metal ions / organic ligands, which theoretically have the characteristics of high stability, high catalytic activity, and multifunctionality. They are widely used in many fields such as energy storage and conversion, gas adsorption and separation, chemical catalysis, and biomedicine.

[0003] However, currently commonly used preparation methods such as hydrothermal synthesis, stirring synthesis, and microwave synthesis methods are difficult to develop medium / high entropy MOFs materials with uniform proportions and controllable content. For example, CN118472355A discloses a high-entropy metal organic framework solid electrolyte modifier and its preparation method and application, wherein the high-entropy MOFs are composed of five specific metal elements (Co, Fe, Zn, Mn and Ni), and the high-entropy MOFs described therein are prepared by a conventional liquid phase method. However, the high-entropy MOFs disclosed therein have a limited controllable range in terms of metal ratio, which can only be adjusted within 0.8 to 1.2. CN116655938A discloses a two-dimensional high-entropy metal organic framework material and its preparation method and application, wherein the two-dimensional high-entropy MOFs contain at least three of Ni, Cu, Co, Zn, Mn, Sb, and Sn, and the ligand contains only at least one. However, the regulation range of ligands and metals is also limited, which is clearly Fe:Co:Ni:Cu:Zn=2.92~13.6:0.73~3.4:1:1:1, and there is no clear definition of the high entropy state. The literature Cryst.GrowthDes.2021,21,5349-5359, Microporous Mesoporous Mater.2024,375,1131611, etc. describe an in-situ thermal solvent-free synthesis method, which successfully prepared single and bimetallic MOFs and controlled the proportion. However, the method does not take into account the competitive reactions between different metals and the influence mechanism of metal elements on the entropy in MOFs, especially the influence on the entropy of periodic porous materials under multiple metal reaction conditions. The literature Angew.Chem.Int.Ed.2019,58(15),5018-5022 etc. reported a mechanochemical synthesis method, which successfully prepared high entropy MOFs of five elements, but the mechanochemical synthesis method adopted could not accurately control the metal element content before and after preparation and modulate it, and the method used required washing, low yield, long time consumption and high cost. Therefore, it is a key technical problem that needs to be solved in this field to clearly define the entropy of MOFs materials and develop a method for preparing medium / high entropy MOFs with an accurately adjustable ratio of metal and organic ligands and a consistent molar ratio of metal elements before and after preparation. Summary of the invention

[0004] In view of this, the present invention proposes a medium / high entropy metal organic framework material and a preparation method thereof, clearly defines medium / high entropy MOFs, and uses them as a universal preparation method in which the ratio of metal types can be widely controlled and the types of ligands can be selected. In addition, the molar ratio of metal ions before and after the preparation of the metal organic framework material is consistent, thereby realizing the green, efficient, low-cost and programmable preparation of medium / high entropy MOFs.

[0005] The medium / high entropy metal organic framework material of the present invention has a periodic porous structure, which is consistent with the topological structure of MOFs composed of a single metal. In addition, different metal elements are evenly distributed in the medium / high entropy metal organic framework material, and the types and contents of the metal elements are fully adjustable, and the types of ligands are selectable.

[0006] The technical solution of the present invention is implemented as follows: On the one hand, the present invention provides a medium / high entropy metal organic framework material, wherein the configuration entropy ΔS of the medium entropy metal organic framework material satisfies 1R<ΔS<1.5R, and the configuration entropy ΔS of the high entropy metal organic framework material satisfies 1R<ΔS<1.5R, and R is a gas constant, which is 8.314;

[0007] The metal ions in the medium / high entropy metal organic framework material are at least four of magnesium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, molybdenum, ruthenium, palladium, silver, cadmium, indium, tin, iridium, rhodium and platinum, and the molar amount of each metal ion is 10% to 70% of the total molar amount of metal ions, and the ratio of the total molar amount of metal ions to the molar amount of organic ligands is 1:2 to 8.

[0008] Based on the above technical solution, preferably, ΔS is calculated by the following formula:

[0009]

[0010] n is the total number of metal types, n≥4; i is the metal type; X i is the molar fraction of the metal in the metal-organic framework; m is the total number of organic ligands, m≥1; Y j is the molar fraction of the jth ligand in the metal organic framework; a ij is the reaction probability constant of the i-th metal and the j-th ligand, which depends on the kinetic constants of different reaction environments; δ is the topological factor, which depends on the topological structure, specifically δ = V × MR, V is the van der Waals volume of the topological structure unit, MR is the number of nodes of the topological structure unit, and δ>1.

[0011] On the basis of the above technical scheme, preferably, the organic ligand in the medium / high entropy metal organic framework is a compound containing imidazole, selected from one or two of alkyl imidazole, halogenated imidazole, phenyl imidazole, polyazole and purine, and can be specifically selected from imidazole, 2-methyl imidazole, 2-ethyl imidazole, 2-propyl imidazole, 2-chloro imidazole, 2-bromo imidazole, 2-nitro imidazole, 2-mercapto imidazole, 2-trifluoromethyl imidazole, 2-phenyl imidazole, 4-methyl imidazole, 4-chloro imidazole, 4-bromo imidazole, 4-nitro imidazole, One or two of imidazole, 4,5-dichloroimidazole, 2-imidazole-carboxaldehyde, 2-imidazole-carboxylic acid, benzimidazole, 2-methylbenzimidazole, 2-aminobenzimidazole, 1H-1,2,3-triazole, 1,2,4-triazole, 3-methyl-1,2,4-triazole, 3,5-dimethyl-1,2,4-triazole, tetrazole, 5-methyltetrazole, 5-aminotetrazole, pentazole, benzotriazole, 4-azabenzimidazole, 5-azabenzimidazole, and 1H-purine.

[0012] In a second aspect, the present invention provides a method for preparing a medium / high entropy metal organic framework material, comprising the following steps:

[0013] S1, mixing the compound containing metal ions and the organic ligand uniformly and then grinding to obtain a precursor;

[0014] S2. The precursor is evenly spread in an alumina crucible, and then placed in a tube furnace, and heated under an inert atmosphere or vacuum conditions to perform a solid phase reaction to obtain a medium / high entropy metal organic framework material.

[0015] In a liquid phase environment, since metal ions react with organic ligands in a high mobility environment, the reaction kinetic constants (k) of different metal ions and organic ligands are too different. Although a variety of metals and ligands are added, the entropy (ΔS) of the MOFs material obtained at this time will be reduced and will not meet the definition of medium / high entropy materials. Therefore, the medium / high entropy metal organic framework provided by the present invention is prepared by a solid phase method, which can balance the reaction kinetics of different metals and organic ligands, and the obtained material entropy value is higher.

[0016] The preparation method provided by the present invention allows the metal compound and the organic ligand to exist in a molten state, and has the characteristics of low diffusion capacity and high external field energy. In the solid phase reaction, the metal compound is ionized at low temperature to form metal ions as solvents, and the organic ligands are fully melted as solutions. Different metal ions can fully react with the local surrounding solvents (organic ligands) under the assistance of the thermal field, so that the k ij The difference is small enough, that is, the k value is small, so that the entropy value of the metal-organic framework is high enough.

[0017] On the basis of the above technical solution, preferably, the molar ratio of the total amount of the metal compound to the organic ligand is 1:2-8, and the mixture is ground in an agate mortar for more than 3 minutes after being weighed.

[0018] Preferably, the molar ratio of the total amount of metal oxide to the organic ligand is 1:6, and the grinding time is 5 minutes.

[0019] On the basis of the above technical scheme, preferably, in step S2, during the solid phase reaction, the heating program is: heating at a heating rate of 1 to 10°C / min at room temperature until the temperature exceeds the melting point of the metal oxide and reaches above 140°C, and keeping warm for more than 30 minutes, then heating at a heating rate of 1 to 10°C / min until the temperature exceeds the metal organic framework solid phase complexation reaction temperature, and keeping warm for more than 30 minutes.

[0020] Preferably, the temperature is raised to 140° C. at 5° C. / min at room temperature, kept at that temperature for 10 minutes, then raised to the average of the melting and boiling points of the organic ligand at 5° C. / min, and kept at that temperature for 60 minutes.

[0021] On the basis of the above technical solution, preferably, in step S2, the inert gas is one of nitrogen, carbon dioxide, helium, neon, argon, and krypton, and the gas flow rate is 50 to 200 cc / min; the vacuum condition is a vacuum degree of less than 1×10 -3 Pa.

[0022] On the basis of the above technical scheme, preferably, the metal compound is one or more of a metal oxide, a metal nitrate, a metal chloride, a metal acetate and a metal acetylacetone complex, and can be specifically selected from magnesium oxide, calcium oxide, titanium oxide, vanadium oxide, chromium oxide, manganese oxide, iron oxide, cobalt oxide, nickel oxide, copper oxide, zinc oxide, zirconium oxide, molybdenum oxide, ruthenium oxide, palladium oxide, silver oxide, cadmium oxide, indium oxide, tin oxide, iridium oxide, rhodium oxide, platinum oxide; magnesium nitrate, calcium nitrate, manganese nitrate, iron nitrate, cobalt nitrate, nickel nitrate, copper nitrate, zinc nitrate, palladium nitrate, silver nitrate, cadmium nitrate, tin nitrate; magnesium chloride, calcium chloride, titanium chloride, vanadium chloride, chromium chloride, manganese chloride, Ferric chloride, cobalt chloride, nickel chloride, copper chloride, zinc chloride, zirconium chloride, molybdenum chloride, ruthenium chloride, palladium chloride, silver chloride, cadmium chloride, indium chloride, tin chloride, iridium chloride, platinum chloride; magnesium acetate, calcium acetate, manganese acetate, ferrous acetate, cobalt acetate, nickel acetate, copper acetate, zinc acetate, ruthenium acetate, palladium acetate, silver acetate, cadmium acetate, indium acetate, tin acetate, iridium acetate, platinum acetate; at least four of magnesium acetylacetonate, titanium acetylacetonate, vanadium acetylacetonate, chromium acetylacetonate, manganese acetylacetonate, iron acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate, zinc acetylacetonate, zirconium acetylacetonate, molybdenum acetylacetonate, ruthenium acetylacetonate, rhodium acetylacetonate, palladium acetylacetonate, silver acetylacetonate, and cadmium acetylacetonate.

[0023] On the basis of the above technical solutions, preferably, the molar ratio of the metal ions before and after the preparation of the metal organic framework material is consistent, and the metal elements are evenly distributed in the material.

[0024] In a third aspect, the present invention provides an application of a medium / high entropy metal organic framework material in the fields of energy storage and conversion, gas adsorption and separation, chemical catalysis, and biomedicine.

[0025] The application of a medium / high entropy metal organic framework material and a preparation method thereof in gas adsorption has the following beneficial effects compared with the prior art:

[0026] (1) The medium / high entropy metal organic framework provided by the present invention has the characteristics of uniform distribution of metal elements, precise modulation, and replaceable organic ligands. The different metals in the medium / high entropy MOFs materials change the original structure, and the material obtains more excellent gas adsorption performance.

[0027] (2) The preparation method used in the present invention can use a variety of different metals to replace the original single metal synthesized MOFs materials, and can accurately control the type and proportion of metals in medium / high entropy MOFs, as well as the structure and performance of the obtained samples.

[0028] (3) In the early stage of medium / high entropy MOFs preparation, the present invention forms a large number of seed crystals by fully mixing through physical grinding, and completes the further growth process with the assistance of thermal field. By regulating the holding time during the mixed metal all-solid phase synthesis process, the particle size of the medium / high entropy MOF crystals can be effectively controlled, so that the particle size of the product powder can be adjusted in the range of nanometer to micrometer.

[0029] (4) The present invention adopts a mixed metal all-solid-phase synthesis method to universally synthesize a variety of medium / high entropy MOFs materials, achieving solvent-free, high-yield, low-cost preparation of medium / high entropy MOFs materials, short synthesis time, simple steps, and is suitable for industrial-grade scale-up production. By regulating the all-solid-phase thermal synthesis parameters including the types (more than 4 types) and proportions (10% to 70%) of organic ligands and metal compounds, as well as the reaction temperature, insulation time, and atmosphere, the medium / high entropy MOFs material phase and micro-nano structure design is achieved, achieving the purpose of efficiently customizing the types, structural parameters, and performance of medium / high entropy MOFs materials.

[0030] (5) Compared with the medium / high entropy MOFs materials prepared by the existing method, the medium / high entropy MOFs materials prepared by the present invention have high-temperature thermal stability, can still maintain structural performance stability at 200-500°C, and can exist stably for a long time in different synthetic pH ranges and in air. It has broad application prospects in gas adsorption and separation, catalysis, fluorescence and sensing, chiral structure and function, membrane separation / catalysis and devices, ion conductors, biomedicine and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 The Mn prepared in Example 1 0.25 Co 0.25 Ni 0.25 Zn 0.25 - Metal ratio diagram of MOF materials before and after preparation;

[0033] Figure 2 The Mn prepared in Example 1 0.25 Co 0.25 Ni 0.25 Zn 0.25 -XRD spectra of MOF-MOF materials;

[0034] Figure 3 The Mn prepared in Example 2 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 - Metal ratio diagram of MOF materials before and after preparation;

[0035] Figure 4 The Mn prepared in Example 2 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -XRD spectrum of MOF materials;

[0036] Figure 5 The Mn prepared in Example 3 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 - Metal ratio diagram of MOF materials before and after preparation;

[0037] Figure 6 The Mn prepared in Example 3 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu0.1 Zn 0.3 -XRD spectrum of MOF materials;

[0038] Figure 7 The Mn prepared in Example 1 0.25 Co 0.25 Ni 0.25 Zn 0.25 -Morphology of MOF materials taken by scanning electron microscope;

[0039] Figure 8 The Mn prepared in Example 1 0.25 Co 0.25 Ni 0.25 Zn 0.25 -CO2 adsorption curve of MOF material characterized by fully automatic specific surface area tester. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments. If the specific experimental conditions are not indicated in the embodiments, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company: the reagents, consumables, etc. used in the following embodiments, unless otherwise specified, can be obtained through commercial channels.

[0042] Example 1

[0043] This embodiment provides a Mn 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF material and programmable preparation method thereof, specifically comprising the following steps:

[0044] S1. Mix manganese acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate and zinc acetylacetonate in a molar ratio of 1:1:1:1, add 2-methylimidazole so that the molar ratio of the total amount of metal to the organic ligand is 1:4, and physically grind in a mortar into a fine powder with uniform color to obtain a precursor;

[0045] S2, the precursor obtained in step S1 is evenly spread in an alumina crucible, and then the alumina crucible is placed in a tube furnace, and a protective atmosphere is introduced for heating treatment. The specific process conditions are: heating to 150°C at a heating rate of 3°C / min at room temperature, and then heating to 220°C at a heating rate of 5°C / min, and keeping warm for 1.5h. The protective atmosphere is nitrogen, and the gas flow rate is 100cc / min. After the heating is completed, the furnace is cooled to room temperature to obtain Mn 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF materials.

[0046] After testing, the Mn prepared in this embodiment 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF has a yield of about 80% and can remain thermally stable in water or other solvents within a temperature range of 100 to 600°C. Figure 1 Mn is obtained in this example 0.25 Co 0.25 Ni 0.25 Zn 0.25 -The metal ratio of MOF material before and after preparation, where the metal ratio after preparation is detected by inductively coupled plasma emission spectrometer, showing that this method has a significant effect on Mn 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF metal ratio has better control. Figure 2 The Mn prepared in this example 0.25 Co 0.25 Ni 0.25 Zn 0.25 -XRD spectrum of MOF material shows that the obtained material is Mn 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF, no impurities, purity over 95%. According to calculation, Mn 0.25 Co 0.25 Ni 0.25 Zn 0.25 -The entropy value of MOF is 1.22R, which is a medium entropy material.

[0047] Figure 1 The Mn prepared in Example 1 0.25 Co 0.25 Ni 0.25 Zn 0.25 -The metal ratio diagram of MOF material before and after preparation, where the molar ratio after preparation is obtained by inductively coupled plasma spectroscopy (ICP) test.0.25 Co 0.25 Ni 0.25 Zn 0.25 -The metal content of the MOF material is consistent in molar ratio before and after preparation, indicating the programmable characteristics of the metal element ratio of the programmable preparation method provided by the present invention. Compared with the mechanochemical synthesis method described in the document Angew.Chem.Int.Ed.2019,58(15),5018-5022, the solid phase synthesis method provided by the present invention can better control the metal ratio in MOFs, specifically, the fluctuation of the metal element molar ratio before and after preparation is less than 5% (the literature is greater than 10%).

[0048] Figure 2 The Mn prepared in Example 1 0.25 Co 0.25 Ni 0.25 Zn 0.25 -XRD spectrum of MOF material, as can be seen from the figure, the Mn 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF materials have no other peaks compared with the standard XRD of MOF materials composed of single metals, indicating that Mn 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF was successfully prepared and the periodic porous structure of MOFs materials was maintained.

[0049] Example 2

[0050] This embodiment provides a Mn 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -MOF material and programmable preparation method thereof, specifically comprising the following steps:

[0051] S1. Mix manganese acetylacetonate, iron acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate, and zinc acetylacetonate in a molar ratio of 2:1:2:2:1:2, add 2-methylimidazole so that the molar ratio of the mixed metal to the organic ligand is 1:6, and physically grind in a mortar into a fine powder with uniform color to obtain a precursor;

[0052] S2, the precursor obtained in step S1 is evenly spread in an alumina crucible, and then the alumina crucible is placed in a tube furnace, and a reducing atmosphere is introduced for pyrolysis treatment. The specific process conditions are: heating to 150°C at a heating rate of 3°C / min at room temperature, keeping warm for 1h, and then heating to 220°C at a heating rate of 5°C / min, keeping warm for 2h, the protective atmosphere is nitrogen, the gas flow rate is 100cc / min, and after the heating is completed, the furnace is cooled to room temperature to obtain Mn 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -MOF materials.

[0053] After testing, the Mn prepared in this embodiment 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -MOF purity can reach more than 95%, the yield is about 85%, and it can still remain thermally stable in water or other solvents within the temperature range of 100-600°C. Figure 3 Mn is obtained in this example 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -The metal ratio of MOF material before and after preparation, where the metal ratio after preparation is detected by inductively coupled plasma emission spectrometer, showing that this method has a significant effect on Mn 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -MOF metal ratio has better control. Figure 4 The prepared Mn 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -XRD spectrum of MOF material. After calculation, Mn 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -The entropy value of MOF is 2.27R, which is a high entropy material.

[0054] By comparison, Example 1 and this example fully illustrate that the method is adjustable for the metal types in medium / high entropy metal organic framework materials.

[0055] Figure 3 The Mn prepared in Example 2 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -The metal ratio diagram of MOF material before and after preparation, where the molar ratio after preparation is obtained by ICP test analysis. 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -The metal content of the MOF material is consistent in molar ratio before and after preparation, which shows that the programmable preparation method provided by the present invention has programmable characteristics for the types and ratios of metal elements. Compared with the mechanochemical synthesis method described in the document Angew.Chem.Int.Ed.2019,58(15),5018-5022, the solid phase synthesis method provided by the present invention can better control the metal ratio in MOFs, specifically, the fluctuation of the molar ratio of metal elements before and after preparation is less than 4% (the literature is greater than 10%).

[0056] Figure 4 The Mn prepared in Example 2 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -XRD spectrum of MOF material, as can be seen from the figure, the Mn 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -MOF materials have no other peaks compared with the standard XRD of MOF materials composed of single metals, indicating that Mn 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -MOF was successfully prepared and the periodic porous structure of MOFs materials was maintained.

[0057] Comparative Example 1 and combined Figure 1 , 2 , 3, and 4 show that the programmable preparation method can regulate the types of metal elements, and the content of each metal element remains substantially unchanged before and after preparation.

[0058] Example 3

[0059] This embodiment provides a Mn 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 -MOF material and programmable preparation method thereof, specifically comprising the following steps:

[0060] S1. Mix manganese acetylacetonate, iron acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate, and zinc acetylacetonate in a molar ratio of 1:1:3:1:1:3, add 2-methylimidazole so that the molar ratio of the mixed metal to the organic ligand is 1:6, and physically grind in a mortar into a fine powder with uniform color to obtain a precursor;

[0061] S2, the precursor obtained in step S1 is evenly spread in an alumina crucible, and then the alumina crucible is placed in a tube furnace, and a reducing atmosphere is introduced for pyrolysis treatment. The specific process conditions are: heating to 150°C at a heating rate of 3°C / min at room temperature, keeping warm for 1h, and then heating to 220°C at a heating rate of 5°C / min, keeping warm for 2h, the protective atmosphere is nitrogen, the gas flow rate is 100cc / min, and after the heating is completed, the furnace is cooled to room temperature to obtain Mn 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 -MOF materials.

[0062] After testing, the Mn prepared in this embodiment 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 -MOF purity can reach more than 95%, the yield is about 80%, and it can still remain thermally stable in water or other solvents within the temperature range of 100-600°C. Figure 5 Mn is obtained in this example 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 -The metal ratio of MOF material before and after preparation, where the metal ratio after preparation is detected by inductively coupled plasma emission spectrometer, showing that this method has a significant effect on Mn 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3-MOF metal ratio has better control. Figure 6 The prepared Mn 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 -XRD spectrum of MOF material. After calculation, Mn 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 -The entropy value of MOF is 2.32R, which is a high entropy material.

[0063] By comparison, Example 2 and this example fully illustrate that the method can adjust the metal ratio in medium / high entropy metal organic framework materials.

[0064] Figure 5 The Mn prepared in Example 3 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 -The metal ratio diagram of MOF material before and after preparation, where the molar ratio after preparation is obtained by ICP test analysis. 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 The metal content of the MOF material is consistent in molar ratio before and after preparation, indicating that the programmable preparation method provided by the present invention can accurately modulate the ratio of metal elements. 0.2 Fe 0.1 Co 0.2 Ni 0.2 Cu 0.1 Zn 0.2 -MOF, this method can accurately program the metal molar ratio in MOFs.

[0065] Figure 6 The Mn prepared in Example 3 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 -XRD spectrum of MOF material, as can be seen from the figure, the Mn 0.1 Fe 0.1 Co 0.3 Ni0.1 Cu 0.1 Zn 0.3 -MOF materials have no other peaks compared with the standard XRD of MOF materials composed of single metals, indicating that Mn 0.1 Fe 0.1 Co 0.3 Ni 0.1 Cu 0.1 Zn 0.3 -MOF was successfully prepared and the periodic porous structure of MOFs materials was maintained.

[0066] Comparative Example 2 and combined Figure 3 , 4 , 5, and 6 show that the programmable preparation method can regulate the content of metal elements, and the content of each metal element remains substantially unchanged before and after preparation.

[0067] Example 4

[0068] This embodiment provides a Mn 0.1 Co 0.1 Cu 0.1 Zn 0.7 -MOF material and programmable preparation method thereof, specifically comprising the following steps:

[0069] S1. Mix manganese acetate, cobalt acetate, copper acetate and zinc acetate in a molar ratio of 1:1:1:7, add benzimidazole so that the molar ratio of the mixed metal to the organic ligand is 1:8, and grind them in a mortar to form a fine powder with uniform color, thereby obtaining a precursor;

[0070] S2, the precursor obtained in step S1 is evenly spread in an alumina crucible, and then the alumina crucible is placed in a tube furnace, and a reducing atmosphere is introduced for pyrolysis treatment. The specific process conditions are: heating to 155°C at a heating rate of 5°C / min at room temperature, keeping warm for 1h, and then heating to 289°C at a heating rate of 8°C / min, keeping warm for 2h, the protective atmosphere is nitrogen, the gas flow rate is 180cc / min, and after the heating is completed, the furnace is cooled to room temperature to obtain Mn 0.25 Co 0.25 Cu 0.25 Zn 0.25 -MOF materials.

[0071] After testing, the Mn prepared in this embodiment 0.1 Co 0.1 Cu 0.1 Zn 0.7 -MOF has a yield of about 80%, and can remain thermally stable in water or other solvents within a temperature range of 100-400°C. 0.1 Co 0.1Cu 0.1 Zn 0.7 -MOF materials have the same metal ratio before and after preparation, indicating that this method is effective for Mn 0.1 Co 0.1 Cu 0.1 Zn 0.7 -MOF metal ratio has good control. The obtained material is Mn 0.1 Co 0.1 Cu 0.1 Zn 0.7 -MOF, no impurities, purity of more than 90%. According to calculations, Mn 0.1 Co 0.1 Cu 0.1 Zn 0.7 -The entropy value of MOF is 1.04R, which is a medium entropy material.

[0072] Example 5

[0073] This embodiment provides a Fe 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF material and programmable preparation method thereof, specifically comprising the following steps:

[0074] S1. Mix ferric acetylacetonate, cobalt acetylacetonate, nickel acetylacetonate and zinc acetylacetonate in a molar ratio of 1:1:1:1, add 5-methyltetrazolyl to make the molar ratio of the mixed metal to the organic ligand be 1:2, and grind in a mortar to form a fine powder with uniform color, thereby obtaining a precursor;

[0075] S2, the precursor obtained in step S1 is evenly spread in an alumina crucible, and then the alumina crucible is placed in a tube furnace, and a reducing atmosphere is introduced for pyrolysis treatment. The specific process conditions are: heating to 170°C at a heating rate of 5°C / min at room temperature, keeping warm for 1h, and then heating to 200°C at a heating rate of 10°C / min, keeping warm for 2h, the protective atmosphere is carbon dioxide, the gas flow rate is 100cc / min, and after the heating is completed, the furnace is cooled to room temperature to obtain Fe 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF materials.

[0076] After testing, the Fe prepared in this embodiment 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF has a yield of about 70%, and can remain thermally stable in water or other solvents within a temperature range of 100-250°C. 0.25 Co 0.25Ni 0.25 Zn 0.25 -MOF materials have the same metal ratio before and after preparation, indicating that this method is effective for Fe 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF metal ratio has good control. The obtained material is Fe 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF, no impurities, purity over 95%. According to calculation, Mn 0.25 Co 0.25 Cu 0.25 Zn 0.25 -The entropy value of MOF is 1.22R, which is a medium entropy material.

[0077] Example 6

[0078] This embodiment provides a Mn 0.1 Fe 0.1 Co 0.2 Ni 0.1 Cu 0.1 Zn 0.3 Cd 0.1 -MOF material and programmable preparation method thereof, specifically comprising the following steps:

[0079] S1. Mix manganese chloride, iron chloride, cobalt chloride, nickel chloride, copper chloride, zinc chloride and cadmium chloride in a molar ratio of 1:1:2:1:1:3:1, add 2-chloroimidazole so that the molar ratio of the mixed metal to the organic ligand is 1:6, and physically grind in a mortar into a fine powder with uniform color to obtain a precursor;

[0080] S2, the precursor obtained in step S1 is evenly spread in an alumina crucible, and then the alumina crucible is placed in a tube furnace, and a reducing atmosphere is introduced for pyrolysis treatment. The specific process conditions are: heating to 160°C at a heating rate of 10°C / min at room temperature, keeping warm for 1h, and then heating to 221°C at a heating rate of 5°C / min, keeping warm for 2h, the protective atmosphere is neon gas, the gas flow rate is 80cc / min, and after the heating is completed, the furnace is cooled to room temperature to obtain Mn 0.1 Fe 0.1 Co 0.2 Ni 0.1 Cu 0.1 Zn 0.3 Cd 0.1 -MOF materials.

[0081] After testing, the Mn prepared in this embodiment 0.1 Fe 0.1 Co 0.2Ni 0.1 Cu 0.1 Zn 0.3 Cd 0.1 -MOF has a yield of about 80%, and can remain thermally stable in water or other solvents within a temperature range of 100-250°C. 0.1 Fe 0.1 Co 0.2 Ni 0.1 Cu 0.1 Zn 0.3 Cd 0.1 -MOF materials have the same metal ratio before and after preparation, indicating that this method is effective for Mn 0.1 Fe 0.1 Co 0.2 Ni 0. 1Cu 0.1 Zn 0.3 Cd 0.1 -MOF metal ratio has good control. The obtained material is Mn 0.1 Fe 0.1 Co 0.2 Ni 0.1 Cu 0.1 Zn 0.3 Cd 0.1 -MOF, no impurities, purity over 95%. According to calculation, Mn 0.1 Fe 0.1 Co 0.2 Ni 0.1 Cu 0.1 Zn 0.3 Cd 0.1 -The entropy value of MOF is 2.65R, which is a high entropy material.

[0082] Example 7

[0083] This embodiment provides a Co 0.4 Ni 0.1 Cu 0.2 Zn 0.3 -MOF material and programmable preparation method thereof, specifically comprising the following steps:

[0084] S1, cobalt acetylacetonate, nickel acetylacetonate, copper acetylacetonate, and zinc acetylacetonate are mixed in a molar ratio of 4:1:2:3, and 2-methylimidazole and benzimidazole are mixed in a ratio of 1:1, and then the molar ratio of the mixed metal to the mixed organic ligand is 1:6, and the mixture is placed in a mortar and physically ground into a fine powder with uniform color to obtain a precursor;

[0085] S2, the precursor obtained in step S1 is evenly spread in an alumina crucible, and then the alumina crucible is placed in a tube furnace, and a reducing atmosphere is introduced for pyrolysis treatment. The specific process conditions are: heating to 145°C at a heating rate of 3°C / min at room temperature, keeping warm for 1h, and then heating to 255°C at a heating rate of 5°C / min, keeping warm for 2h, the protective atmosphere is argon, the gas flow rate is 150cc / min, and after the heating is completed, the furnace is cooled to room temperature to obtain Co 0.4 Ni 0.1 Cu 0.2 Zn 0.3 -MOF materials.

[0086] After testing, the Co prepared in this embodiment 0.4 Ni 0.1 Cu 0.2 Zn 0.3 -MOF has a yield of about 80%, and can remain thermally stable in water or other solvents within a temperature range of 100-250°C. 0.4 Ni 0.1 Cu 0.2 Zn 0.3 -MOF materials have the same metal ratio before and after preparation and have a grid structure with mixed ligands, showing that this method is effective for Co 0.4 Ni 0.1 Cu 0.2 Zn 0.3 -MOF metal ratio has good control. The obtained material is Co 0.4 Ni 0.1 Cu 0.2 Zn 0.3 -MOF, no impurities, purity of more than 95%. According to calculations, Co 0.4 Ni 0.1 Cu 0.2 Zn 0.3 -The entropy value of MOF is 2.08R, which is a high entropy material.

[0087] Example 8

[0088] This embodiment provides a Zn 0.5 Ru 0.1 R 0.1 Pb 0.1 Ag 0.1 Pt 0.1 -MOF material and programmable preparation method thereof, specifically comprising the following steps:

[0089] S1, zinc acetylacetonate, ruthenium (III) acetylacetonate, rhodium (III) acetylacetonate, palladium (II) acetylacetonate, silver (I) acetylacetonate, and platinum (II) acetylacetonate are mixed in a molar ratio of 5:1:1:1:1:1, and benzotriazole is added to make the molar ratio of the mixed metal to the organic ligand be 1:6, and the mixture is placed in a mortar and physically ground into a fine powder with uniform color to obtain a precursor;

[0090] S2, the precursor obtained in step S1 is evenly spread in an alumina crucible, and then the alumina crucible is placed in a tube furnace, and a reducing atmosphere is introduced for pyrolysis treatment. The specific process conditions are: heating to 150°C at a heating rate of 1°C / min at room temperature, keeping warm for 1h, and then heating to 164°C at a heating rate of 1°C / min, keeping warm for 2h, the protective atmosphere is krypton gas, the gas flow rate is 200cc / min, and after the heating is completed, the furnace is cooled to room temperature to obtain Zn 0.5 Ru 0.1 R 0.1 Pb 0.1 Ag 0.1 Pt 0.1 -MOF materials.

[0091] After testing, the Zn prepared in this embodiment 0.5 Ru 0.1 R 0.1 Pb 0.1 Ag 0.1 Pt 0.1 -MOF has a yield of about 80%, and can remain thermally stable in water or other solvents within a temperature range of 100-250°C. 0.5 Ru 0.1 R 0.1 Pb 0.1 Ag 0.1 Pt 0.1 -MOF materials have the same metal ratio before and after preparation and have a grid structure with mixed ligands, showing that this method is effective for Zn 0.5 Ru 0.1 R 0.1 Pb 0.1 Ag 0.1 Pt 0.1 -MOF metal ratio has good control. The obtained material is Zn 0.5 Ru 0.1 R 0.1 Pb 0.1 Ag 0.1 Pt 0.1 -MOF, no impurities, purity of more than 90%. According to calculations, Zn 0.5 Ru 0.1 R 0.1 Pb 0.1 Ag0.1 Pt 0.1 -The entropy value of MOF is 2.39R, which is a high entropy material.

[0092] Application of medium / high entropy metal organic framework materials in carbon dioxide adsorption:

[0093] Figure 7 The Mn prepared in Example 1 0.25 Co 0.25 Ni 0.25 Zn 0.25 -MOF material morphology image taken by scanning electron microscope. It can be seen from the figure that the primary particles are regular dodecahedrons (diameter of about 1-3 μm), the secondary particles are irregular polyhedrons (diameter of about 200-500 nm), and the secondary particles are a small number of initially grown unit cells dispersed on the surface and around the primary particles.

[0094] The regular dodecahedron morphology of the primary particles has a higher surface area, which increases the contact area with gas molecules and is conducive to the diffusion and contact of gas molecules. Particles with a moderate particle size range (1 to 3 μm) can ensure good dispersibility of the material in actual use, avoid clogging, and increase the specific surface area, which is conducive to gas adsorption. The small particle size of 200 to 500 nm provides a higher specific surface area and more porous structure, further improving the material's ability to contact gas. This multi-level structure (composed of primary regular dodecahedron particles and secondary irregular polyhedron particles) is conducive to the diffusion of gas molecules through micropores and mesopores, and quickly reaching the internal adsorption sites.

[0095] Figure 8 The Mn prepared in Example 1 0.25 Co 0.25 Ni 0.25 Zn 0.25 -The carbon dioxide adsorption curve of the MOF material characterized by the fully automatic specific surface area tester shows better carbon dioxide adsorption performance than the low-entropy (single metal) MOFs materials reported in Sep. Purif. Technol. 2025, 358 (B), 130389, Molecules, 2023, 28 (20), 7056, etc., and has certain application potential in the field of waste gas adsorption in industry, automobiles, etc.

[0096] Comparative Example 1

[0097] This embodiment provides a Fe 0.05 Co 0.05 Ni 0.05 Cu 0.05 Zn 0.8 -MOF material and programmable preparation method thereof, specifically comprising the following steps:

[0098] S1, ferrous acetate, cobalt acetate, nickel acetate, copper acetylacetonate, and zinc oxide are mixed in a molar ratio of 1:1:1:1:16, and 2-methylimidazole is added to make the molar ratio of the mixed metal to the organic ligand be 1:4, and the mixture is placed in a mortar and physically ground into a fine powder with uniform color to obtain a precursor;

[0099] S2, the precursor obtained in step S1 is evenly spread in an alumina crucible, and then the alumina crucible is placed in a tube furnace, and a reducing atmosphere is introduced for pyrolysis treatment. The specific process conditions are: heating to 100°C at a heating rate of 1°C / min at room temperature, keeping warm for 1h, and then heating to 220°C at a heating rate of 5°C / min, keeping warm for 1h, the protective atmosphere is krypton gas, the gas flow rate is 100cc / min, and after the heating is completed, the furnace is cooled to room temperature to obtain Fe 0.05 Co 0.05 Ni 0.05 Cu 0.05 Zn 0.8 -MOF materials.

[0100] After testing, the Fe prepared in this embodiment 0.05 Co 0.05 Ni 0.05 Cu 0.05 Zn 0.8 -MOF has a yield of about 90%, and can remain thermally stable in water or other solvents within a temperature range of 100-500°C. 0.05 Co 0.05 Ni 0.05 Cu 0.05 Zn 0.8 -MOF materials have the same metal ratio before and after preparation and have a mixed ligand grid structure, showing that this method is effective for Fe 0.05 Co 0.05 Ni 0.05 Cu 0.05 Zn 0.8 -MOF metal ratio has good control. The obtained material is Fe 0.05 Co 0.05 Ni 0.05 Cu 0.05 Zn 0.8 -MOF, no impurities, purity over 90%. 0.05 Co 0.05 Ni 0.05 Cu 0.05 Zn 0.8 -MOF has an entropy value of 0.91R, which is a low entropy material. The comparative example illustrates the controllable preparation of other low entropy materials of the same type by the programmable preparation method.

[0101] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A medium / high entropy metal organic framework material, characterized in that: The configuration entropy ΔS of the medium entropy metal organic framework material satisfies 1R<ΔS<1.5R, and the configuration entropy ΔS>1.5R of the high entropy metal organic framework material, where R is the gas constant; The metal ions in the medium / high entropy metal organic framework material are at least four of magnesium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, zirconium, molybdenum, ruthenium, palladium, silver, cadmium, indium, tin, iridium, rhodium and platinum, the molar amount of each metal ion is 10% to 70% of the total molar amount of metal ions, and the ratio of the total molar amount of metal ions to the molar amount of organic ligands is 1:2 to 8.

2. The medium / high entropy metal organic framework material according to claim 1, characterized in that The ΔS is calculated by the following formula: n is the total number of metal types, n≥4; i is the metal type; X i is the molar fraction of the metal in the metal-organic framework; m is the total number of organic ligands, m≥1; Y j is the molar fraction of the jth ligand in the metal organic framework; a ij is the reaction probability constant of the i-th metal and the j-th ligand, which depends on the kinetic constants of different reaction environments; δ is the topological factor, which depends on the topological structure, δ = V × MR, V is the van der Waals volume of the topological structure unit, MR is the number of nodes of the topological structure unit, and δ>1.

3. The medium / high entropy metal organic framework material according to claim 2, characterized in that: The organic ligand in the medium / high entropy metal organic framework is a compound containing imidazole, which is selected from one or two of alkyl imidazole, halogenated imidazole, phenyl imidazole, polyazole and purine.

4. A method for preparing a medium / high entropy metal organic framework material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing the compound containing metal ions and the organic ligand uniformly and then grinding to obtain a precursor; S2. The precursor is evenly spread in an alumina crucible, and then placed in a tube furnace, and heated under an inert atmosphere or vacuum conditions to perform a solid phase reaction to obtain a medium / high entropy metal organic framework material.

5. The method for preparing a medium / high entropy metal organic framework material according to claim 4, characterized in that: In step S2, during the solid phase reaction, the heating program is: heating at a heating rate of 1 to 10°C / min at room temperature until the temperature exceeds the melting point of the metal compound and reaches above 140°C, and keeping warm for more than 30 minutes, then heating at a heating rate of 1 to 10°C / min until the temperature exceeds the metal organic framework solid phase complexation reaction temperature, and keeping warm for more than 30 minutes.

6. The method for preparing a medium / high entropy metal organic framework material according to claim 4, characterized in that: In step S2, the inert gas is one of nitrogen, carbon dioxide, helium, neon, argon, and krypton, and the gas flow rate is 50 to 200 cc / min; the vacuum condition is a vacuum degree of less than 1×10 -3 Pa.

7. The method for preparing a medium / high entropy metal organic framework material according to claim 4, characterized in that: The metal compound is one or more of metal oxides, metal nitrates, metal chlorides, metal acetates and metal acetylacetonate complexes.

8. The method for preparing a medium / high entropy metal organic framework material according to claim 4, characterized in that: The molar ratio of the metal ions before and after the preparation of the metal organic framework material changes by less than 5%, and the metal elements are evenly distributed in the material.

Citation Information

Patent Citations

  • Method for all-solid-phase synthesis of MOFs material

    CN115975209A

  • High-entropy metal organic framework material as well as preparation method and application thereof

    CN116903877A

Cited By

  • A mixed-ligand zeolitic imidazolate framework material, and methods of making and using the same

    CN122726454A